2012
DOI: 10.1108/17590831211206617
|View full text |Cite
|
Sign up to set email alerts
|

The influence of religion on Islamic mobile phone banking services adoption

Abstract: PurposeThe purpose of this paper is to explore the effects religious affiliation and commitment have on Southeast Asian young adults' intention to adopt Islamic mobile phone banking.Design/methodology/approachAn online self‐administered survey was distributed to Southeast Asian young adults through convenience and snowball sampling and a total of 135 responses obtained.FindingsThe study found Islamic mobile phone banking to be a novelty service, with little consumer awareness and experience, especially among n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 46 publications
(75 reference statements)
1
81
0
4
Order By: Relevance
“…Yet, religion has long been acknowledged as a strong influence on consumers’ decision making. Religion has been found to help explain consumers’ choice in using products and their response to advertising appeals (Fam, Waller, & Erdogan, ; Hirschman, ; Sun, Goh, Fam, & Xue, ).…”
mentioning
confidence: 99%
“…Yet, religion has long been acknowledged as a strong influence on consumers’ decision making. Religion has been found to help explain consumers’ choice in using products and their response to advertising appeals (Fam, Waller, & Erdogan, ; Hirschman, ; Sun, Goh, Fam, & Xue, ).…”
mentioning
confidence: 99%
“…TRA is open to modification or extension by altering the path and including additional predictors if it can be shown to capture a greater proportion of variance in intention after the original constructs have been taken into account [31]. This theory is appropriate for this study as it has been shown to be applicable in various other contexts of Islamic marketing such as in the halal food purchasing [35,36], Islamic insurance [37], Islamic pawn shops [38], Islamic home financing [39], Islamic personal financing [37], Islamic credit cards [40] and Islamic mobile phone banking [41].…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 99%
“…Few researchers found that religious factor significantly influence the demand for such services (Metawa & Almossawi, 1998;Lee & Ullah, 2011), while other claimed that religious factor does not affect customer's decision of selecting a bank (Erol & El-Bdour, 1989;Amin et al, 2011;Ghauri et al, 2012). Some studies also found that very few bank customers select Islamic banks strictly due to religion whereas majority of them select Islamic banks due to non religious reasons (Gerrard & Cunningham, 1997;Abdul Hamid & Azmin, 2001;Sun et al, 2012).…”
Section: Religious Factormentioning
confidence: 99%
“…However, while exploring the influence of religion on demand for phone banking services offered by Islamic banks, Sun et al (2012) found that only faithful Muslims prefer Islamic banks due to religious reasons whereas heedlessly religious Muslims and non-Muslims consider utility attributes of the products. In Malaysia, another study explored the factors which encourage bank customer to prefer Islamic banks over conventional banks.…”
Section: Religious Factormentioning
confidence: 99%